Effectiveness of Aloe Vera as a Natural Corrosion Inhibitor for Carbon Steel in Acidic Media - Algathafi Eisay; Seham Nagib; Suleiman Abdelrahim; Shayma Zahwan; Khadeejah Ali; Amaal Miftah (AlQalam Journal of Medical and Applied Sciences, 2025)
This study explores the performance of Aloe Vera extract as a sustainable corrosion inhibitor for carbon steel in sulfuric acid environments. Experimental evaluations were conducted under varying conditions, including inhibitor dosages (0, 12, 20, and 30 mL), acid concentrations (1, 1.5, and 2 M, H2SO4), and temperatures (25, 50, and 70 °C), over extended immersion periods. The results indicate that Aloe vera exhibits high inhibition efficiency exceeding 90% under mild conditions (12 mL in 1 M H2SO4 at 25 °C), while its performance diminishes progressively with increased acid strength and elevated temperatures. The inhibition mechanism is attributed to the adsorption of bioactive constituents from the extract onto the metal surface, forming a passive protective layer. Notably, increased inhibitor dosage partially counteracted the adverse effects of more aggressive environments. These findings highlight Aloe vera as a promising green alternative to synthetic inhibitors, with potential applications in acid pickling, oilfield operations, and other corrosive systems where environmental compatibility is critical.